1977
DOI: 10.1111/j.1651-2227.1977.tb07825.x
|View full text |Cite
|
Sign up to set email alerts
|

LONG‐TERM EFFECT ON MOTHER‐INFANT BEHAVIOUR OF EXTRA CONTACT DURING THE FIRST HOUR POST PARTUM I. First Observations at 36 hours

Abstract: The immediate post partum period may be particularly important for the developing relationship between mother and infant; little is as yet known, however, of the long-term effects of hospital practice during this period. This study examines the effect of extra contact during the first hour following delivery. An extra skin to skin contact and suckling contact was given to 22 primiparous mothers and their infants. One control group of 20 primiparous mothers and infants and a second one of 20 multiparous mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(48 citation statements)
references
References 10 publications
4
41
1
2
Order By: Relevance
“…Amongst these researches, we shall cite those that have compared different conditions of hospitalisation ("rooming-in") and those that have introduced variations likely to show differences in the mother's behaviour, according to whether or not she was allowed an "early contact" or an "extra contact" with her baby (Klaus-Jerauld 1972, De Chateau 1980, De Chateau-Wiberg 1977, Carlsson and Coll 1978. Kennell and Klaus' "Maternal Infant Bonding" (1976) provides a general review of this question.…”
Section: Discussionmentioning
confidence: 98%
“…Amongst these researches, we shall cite those that have compared different conditions of hospitalisation ("rooming-in") and those that have introduced variations likely to show differences in the mother's behaviour, according to whether or not she was allowed an "early contact" or an "extra contact" with her baby (Klaus-Jerauld 1972, De Chateau 1980, De Chateau-Wiberg 1977, Carlsson and Coll 1978. Kennell and Klaus' "Maternal Infant Bonding" (1976) provides a general review of this question.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, interruption of this mother/ infant bonding may negatively influence both the mother's and the child's subsequent behaviour (36,38,39). Thus, both American (36,40) and Swedish (38,39) studies have observed more affectionate behaviour towards the infants by mothers offered extra contact with their babies after delivery as compared with mothers not offered this contact.…”
Section: B)mentioning
confidence: 88%
“…Thus, both American (36,40) and Swedish (38,39) studies have observed more affectionate behaviour towards the infants by mothers offered extra contact with their babies after delivery as compared with mothers not offered this contact. Also, both the American (41,42) and Swedish (43) children in the extra contact groups were found to be more verbally developed than the controls when they were between 2 and 5 years old.…”
Section: B)mentioning
confidence: 91%
“…77,78 The practice of immediate skin-to-skin interaction relates to better infant physiological and neurobehavioral outcomes, positive attachment relationships, and maternal breast-feeding success. 79 However, although several methodological quality issues have engendered questions about some of the benefits (maternal breast milk maturation, infant heart rate), most recently, there is consensus that early skin-to-skin contact carries some clinical benefits, especially regarding breast-feeding outcomes and infant crying. 80 Moreover, a successful vaginal delivery is tolerated psychologically better and, with virtually no surgical recovery time, the policy of early breast feeding may be easier to implement compared with women delivered by CD.…”
Section: Maternal-infant Interactionmentioning
confidence: 99%